ANTIBACTERIAL ACTIVITY AND THIN LAYER CHROMATOGRAPHY PROFILE Muntingia Calabura LEAF EXTRACT AS A MATERIAL CANDIDATE HAND SANITIZER - Santy Pristianingrum; Baiq Lely Zainiati; Iwan Doddy Dharmawibawa (poltekkes kemenkes mataram, 2017)
Abstract : the utilization of antibacterial active substances from several plants is increasingly not only as the ingredients of medicine, but its utilization is also utilized for an antibacterial ingredient for preventive action, one of them is hand sanitizer material. This research focused to find the antibacterial active substances alternative from Muntingia calabura leaves extract. The data were analyzed descriptively including the inhibitory of ethanol absolute extract and ethanol 95% of M. Calabura against isolate clinical bacteria by Kirby Bauer method and the type of coumpund that contains in M.calabura leaf by thin layer chromatography utilizingeluen n-hexan- Methanol. Etanol absolute extract M.calabura leaf showing the average inhibition zone against Pseudomonas aeruginosa 15.67 mm, Staphylococcus aureus 19.33 mm and Escherichia coli 13 mm. While, The etanol extract 95% showing higher inhibition Pseudomonas aeruginosa 19.67 mm, Staphylococcus aureus 19.33 mm and Escherichia coli 16.67 mm. This inhibitory zone was slightly lower than chlorhexidine gluconate with an average of 20-24 mm against the three bacteria that utilized in the test but belongs to the strongly sensitive category for natural materials according to Mukherjee (1988). From thin layer chromatography profile with eluen n-hexan: methanol found three compounds that were in the range of Rf value 0.4; 0.5 and 0.7. The Conclusion for this study is the bioactive material from etanol 95% extract M.calabura leaf can be optimized to the hand sanitizer active compound candidate.